Stress Distribution Pattern in Roots of Incisors with Various Root Resorptions: A Finite Element Study - Oshagh, Morteza (Journal of Dental School, 2019)
Objectives Root resorption is a dangerous side effect in orthodontics, and maxillary incisors are at the highest risk for root resorption. It is important to understand optimal force considerations for patients with altered root lengths.The purpose of this study was to investigate the effects of root length on stress distribution on roots by means of three-dimensional finite element method (FEM). Methods Three dimensional FEM models of maxillary central and lateral incisors were made. Then, root length of the incisors was changed in the increments of 1 mm from 0-4 mm. Applying 50 g (0.5 N) of force perpendicular to the tooth crown simulated uncontrolled tipping. Stresses and strains for each model were calculated and Pearson correlation coefficient was used to analysis the data. Results There were significant correlations between root length of incisors and maximum stress in PDL. In the centrals with various root lengths, maximum stress was between 0.010884 and 0.056520 MPa, and in the laterals, it was between 0.027297 and 0.221040 MPa. By reducing root length of incisors, the maximum stress in buccal apical (r= 0.933,p<0.001 and 0.995, p<0.001 prospectively) and lingual crestal areas (r= 0.974 p=0.005 and 0.992, p=0.001 respectively) were reduced. Conclusion Although in lateral incisors, stress at the lingual crestal area was more than buccal apical area, in central incisors with more than 2 mm resorption, the stress distribution of buccal apical was higher. Therefore, in maxillary central incisors with more root resorption, force control might be even more critical.